BENCANA ALAM DAN PENANGGULANGAN NARASI GAMPO TUJUAH HARI PADANG PANJANG 1926 - Fikrul Hanif Sufyan (Khazanah: Jurnal Sejarah dan Kebudayaan Islam, 2021)
The Padang Panjang earthquake has become a major part of the Minang people's memory in recent times. Those born after the earthquake often remember their birthday, after the strong shaking that lasted for seven days. This paper is prepared based on historical methods, namely heuristics, criticism, interpretation, and historiography. The earthquake that occurred in January 1926 was based on records of reports of the impact of terrible damage. The tsunami, buildings were destroyed, roads were badly damaged, and rail transportation was damaged, not to mention the human casualties who died and were injured. After the damage caused by the earthquake, the Dutch colonial government intervened to provide assistance to earthquake victims. The government is also working hard to rebuild buildings from the rubble of destruction.